2023
DOI: 10.3390/biology12060827
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Quality Control and Male Fertility

Abstract: Mitochondria are pivotal to cellular homeostasis, performing vital functions such as bioenergetics, biosynthesis, and cell signalling. Proper maintenance of these processes is crucial to prevent disease development and ensure optimal cell function. Mitochondrial dynamics, including fission, fusion, biogenesis, mitophagy, and apoptosis, maintain mitochondrial quality control, which is essential for overall cell health. In male reproduction, mitochondria play a pivotal role in germ cell development and any defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 151 publications
0
11
0
Order By: Relevance
“…FIRMAN and SIMMONS [ 46 ] reported that midpiece size is a predictor of swimming speed of Mus musculus domesticus spermatozoa. It is known that RF-EMR can cause cell/sperm apoptosis, and mitochondria are the main initiators of apoptosis [ 47 ]. In addition, RF-EMR promotes increased mitochondrial ROS production and expression of mitochondrial apoptotic markers [ 48 ] with decreased mitochondrial membrane potential [ 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FIRMAN and SIMMONS [ 46 ] reported that midpiece size is a predictor of swimming speed of Mus musculus domesticus spermatozoa. It is known that RF-EMR can cause cell/sperm apoptosis, and mitochondria are the main initiators of apoptosis [ 47 ]. In addition, RF-EMR promotes increased mitochondrial ROS production and expression of mitochondrial apoptotic markers [ 48 ] with decreased mitochondrial membrane potential [ 47 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that RF-EMR can cause cell/sperm apoptosis, and mitochondria are the main initiators of apoptosis [ 47 ]. In addition, RF-EMR promotes increased mitochondrial ROS production and expression of mitochondrial apoptotic markers [ 48 ] with decreased mitochondrial membrane potential [ 47 , 49 ]. Although the exact mechanism of apoptotic changes in spermatozoa, and in somatic cells, is still unknown, one of the signs of apoptosis was described as typical cell shrinkage [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sperm, the remaining mitochondria are concentrated in the midpiece, which is the most proximal region of the human sperm tail 20 . Mitochondria in human sperm are arranged in an end‐to‐end manner forming the structure known as the ‘mitochondrial sheath’ that wraps along the outer dense fibres of the sperm tail 21 . These mitochondria, which are similar in ultrastructure and function to those found in other cells, assume a shape known as the ‘mitochondrial capsule’ 22 .…”
Section: Mitochondria In Spermmentioning
confidence: 99%
“…Interestingly, the preferred pathway in sperm and the extent of its utilization vary among species, in the developmental stage of the germ cell during spermatogenesis and the physiological status of sperm 13 . During its final stage, referred to as spermiogenesis, particularly at the stage of elongated spermatids, OXPHOS is the main energy‐generating pathway 21 . This stage is characterized by extensive remodelling of the cell structure to form the sperm tail and the acrosome, both of which require a significant amount of ATP.…”
Section: Mitochondria In Spermmentioning
confidence: 99%
See 1 more Smart Citation